Dropout in tertiary education in Brazil: An analysis of the effects of the PNAES Bolsa Permanência - Alice Saccaro; Marco Túlio Aniceto França; Paulo de Andrade Jacinto (EconomiA, 2020)
In this article, it is explored whether quota students who were enrolled in presential courses at federal institutions between 2009 and 2012 and received PNAES (National Student Support Program) Bolsa Permanência dropped out less than those quota students who did not receive this benefit. For this analysis, it was used data collected from the Tertiary Education Census and the Difference in Differences approach to look at how different characteristics influence the dropout rate and the chances that a student will receive a Bolsa Permanência. Results show that the chances of receiving the benefit depends on individual and school characteristics, and that the dropout rate among aid recipients is lower than among those who did not receive the benefit.
Keywords: C21; H52; H53; 330; Dropout; Tertiary education; Student aid